Financial and contractual problems of construction projects in Iran - Khoshgoftar, Mohammad; Bakar, Abu Hassan Abu; Osman, Omar (2008)
The construction industry is vital for the development of any country. The pace of the economic growth of any nation can be measured by the development of physical infrastructures, such as buildings, roads and bridges. Rapid and economy completions of projects depend largely upon the availability of timely funds. Most of the clients hire a general contractor through competitive bidding process to do the entire construction work. The research was done on the industrial projects in Iran. This research conducted by questionnaires survey on those who worked in client consultant and contractor companies. Forty eight sets of questionnaires were posted and emailed to large companies in Esfahan at random. The result indicated that the most important contractual problems were: In the documents of tender, some items of the tasks and works in project are not predicted, In the time of the tender, drawing and plans are not complete, contractors have not enough information about all work items in the project and the details about it, In the process of a project execution more new tasks are ordered, some of them need special plans and equipment that contractors are not ready for them. The most important financial problems were: employer financial problem, contractor financial problem, inflation, low price of contract and lack of financial resources. Keywords: Finance, Contract, Esfahan, Iran